2017
DOI: 10.4172/2157-7099.1000474
|View full text |Cite
|
Sign up to set email alerts
|

Co-upregulation of Transforming Growth Factor Beta-1 and Nitric Oxide Synthase in Keloid by comparison to normal human skin-A possible role for TGFβ1 and NOS in pathogenesis of keloid

Abstract: Keloid disease is a benign but progressive form of abnormal wound healing associated with skin fibrosis and can cause a major functional disability and morbidity. TGF beta (TGFβ) and Nitric Oxide (NO) are active biomarkers known to regulate phases of wound healing and have been implicated in pathogenesis of fibrotic disease. There are three isoforms of TGFβ (1, 2 and 3) TGFβ1 and 3 have a crucial role in fibrosis, with TGFβ1 profibrotic and TGFβ3 antifibrotic. NO is produced by Nitric Oxide Synthase (NOS) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Wound repair normally involves iNOS, arginase, and COX‐2 and it is likely that interference with these physiological responses to injury either by inhibitors or inducers of these enzymes could alter the healing process. However delayed healing which occurs under conditions associated with low expression for example, in malnutrition and diabetes (Schaffer, Tantry, Ahrendt, Wasserkrug, & Barbul, ; Schäffer, Tantry, van Wesep, & Barbul, ) or excessive upregulation of these enzymes such as in chronic wounds (S. Abd El‐Aleem et al, ; Seham A. Abd El‐Aleem et al, ; Abd El‐Aleem et al, ; Jude et al, ) might be treated using specific inducers or inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound repair normally involves iNOS, arginase, and COX‐2 and it is likely that interference with these physiological responses to injury either by inhibitors or inducers of these enzymes could alter the healing process. However delayed healing which occurs under conditions associated with low expression for example, in malnutrition and diabetes (Schaffer, Tantry, Ahrendt, Wasserkrug, & Barbul, ; Schäffer, Tantry, van Wesep, & Barbul, ) or excessive upregulation of these enzymes such as in chronic wounds (S. Abd El‐Aleem et al, ; Seham A. Abd El‐Aleem et al, ; Abd El‐Aleem et al, ; Jude et al, ) might be treated using specific inducers or inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Wound repair is regulated by a number of chemical factors such as cytokines, nitric oxide (NO), and prostaglandins (Chang, Liao, & Kuo, ; Dzik, ; Gonzalez et al, ; Tomlinson & Willoughby, ). Previously we have shown that dysregulation of these mediators contributes to abnormal wound healing causing chronicity of the wound (S. Abd El‐Aleem, Muftah, & Jude, ; Abd El‐Aleem et al, ; Jude, Boulton, Ferguson, & Appleton, ) or excessive fibrosis as in keloid (S. Abd El‐Aleem, Abdelwahab, & Osman, ).…”
Section: Introductionmentioning
confidence: 99%
“…In keloid, above all a co-upregulation of TGFß1 and inducible nitric oxide synthase was found. This research article is of great importance, because it gives the possibility to develop a specific antifibrotic pharmacological agent [5].…”
mentioning
confidence: 99%